Empreendedoras do setor de vestuário na região de Maringá : significados, dificuldades e perspectivas de crescimento de PMEs - Guedes, Alexandre Marcelo Coutinho (2012)
The growth of the firm is a phenomenon apparently desirable, since it allows for an increase in wealth and income. Considering that the companies of women entrepreneurs grow less than those of men, this study contributes to the understanding of this gap by means of its objective, which is to study the growth of business from meanings, difficulties and perspectives of women entrepreneurs in the vest industry of the region of Maringá, Cianorte, in the State of Paraná. To achieve this objective, we opted for an exploratory study with a quantitative approach, with the entrepreneurial tied to the unions that represented the sector. Were returned 102 questionnaires and results it was found that the meanings of growth are related to the improvement in the financial results and the management of internal resources, in addition to the biggest competitive capacity. Among the main difficulties are the lack of knowledge of the business since the beginning, for the organization and planning, and professional qualification. And as for the prospects, the entrepreneurs expect with the growth improve personal income, have more quality of life and to achieve as a professional, specifically in this order.